Phenotypic detection of Extended Spectrum Beta-Lactamases and Amp C Beta- Lactamases among nosocomial isolates in a tertiary care hospital - Vijayvergia, V; Sahni, AK; Lall, M; Vijay, K; Khan, ID (Bangladesh Journal of Medical Science, 2013)
Background & objectives: Extended-Spectrum Beta-Lactamases (ESBLs) is an important resistance mechanism in Enterobacteriaceae infections. Lack of standard guidelines from Clinical Laboratory Standards Institute (CLSI) for Amp C beta-lactamase detection poses a problem. This study was undertaken to detect ESBLs by phenotypic tests and Amp C beta-lactamase by inhibitor based method. Material and Methods: 200 consecutive non-repetitive isolates of E.coli, Klebsiella and Proteus from clinical samples were screened for ESBLs as per CLSI guidelines and confirmed by PCDT, DDST and E-tests (AB Biodisk, Biomerieux). Amp C beta lactamases were screened by cefoxitin resistance and confirmed by inhibitor (Cloxacillin) based method. Simultaneous occurrence of Amp C and ESBLs was detected by combined disk test (Neo-Sensitabs and Diatabs). Descriptive and Kappa statistics were used. Results: Out of 200 isolates studied, 131 were initially screened as ESBL producers and later 114 (57%) were confirmed by phenotypic methods. E-Test was found most sensitive phenotypic test as compared to PCDT and DDST. 13 strains resistant to cefoxitin (30?g) were found to be pure Amp C producers. Combined disk test detected 36 to be ESBL and Amp C co-producers. Surprisingly, six isolates found sensitive to cefoxitin disk were confirmed as Amp C producers by cloxacillin disk inhibition test. Conclusion: 57% ESBLs and 27.5% Amp C producers were isolated from nosocomial pathogens showing significant resistance to 3rd generation cephalosporins. Phenotypic confirmation by E-test, PCDT & DDST were useful for ESBL identification and for detection of Amp C, cloxacillin was found to be an effective inhibitor. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13309 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 378-384